How the sexual grooming may have a hand in the controversial marriage between 41-year-old man and 11-year-old girl - Maher, Hana; Md Hashim, Noraini (malaysiandigest.com, 2018)
The marriage between an 11 years old girl and 41 years old man in June 2018 has resulted an outcry across Malaysia particularly when it involved sexual grooming by the man. What is the position under Islamic Law on this issue. Interview conducted on 5pm, 8th July 2018 by Sister Hana Maher